Breaking par: Short-term determinants of yen-dollar swap deviations - Stefan Angrick; Naoko Nemoto (Asian Development Bank Institute (ADBI), 2018)
This paper analyses deviations in yen-dollar cross-currency swap markets between 2007 and 2017. Using weekly-frequency data on money market-related and capital marketrelated financial variables, we analyse how the cross-currency basis is influenced by differences in returns and different types of risk. We study these dynamics using statedependent impulse responses obtained from local projections. Our results show that differences in bond yields, particularly short-term and medium-term government bond yields, are a quantitatively relevant driver of the cross-currency basis in the post-crisis period. We argue that spreads opening up in these markets provide an incentive for cross-border financial flows and corresponding hedging demand, which in turn drive the basis in the post-crisis period. We further find some evidence for the relevance of central bank balance sheet policies, relative corporate bond market performance, and general market volatility. Overall, the impulse responses for the immediate crisis period are considerably more indeterminate and quantitatively less relevant than the responses in the post-crisis state.
Keywords: F31; G15; G2; 330; foreign currency swaps; currency basis; yen-dollar; covered interest parity; international finance